Analytical study of social networking sites usage and social anxiety among physical education students - A’mir, Omar; Alzughailat, Mohannad; Abdel Fattah, Osama; Zureigat, Ayed; Azab, Mahmoud; Jarrd, Maha (International Journal of Public Health Science (IJPHS), 2024)
Social networking sites usages (SNSu) are online platforms used for communication, sharing, and connecting with others. This paper aims to investigate the current status of SNSu among students in physical education college, as well as the differences in SNSu based on gender. Additionally, we aimed to assess the level of social anxiety among the study participants and examine whether it varied by gender and SNSu. We conducted a descriptive survey among 1,109 physical education students (688 females and 421 males) enrolled in public universities. We administered the social anxiety disorder-adult and SNSu questionnaire using Google Forms. We analyzed the data using means, standard deviations, frequencies, percentages, One-way ANOVA, and chi-square tests with a confidence level of 95% (p<0.05). The results of the study showed that both male and female students used social networking sites (SNS) more than 10 times a day, with percentages of 46.3% and 46.1%, respectively. Additionally, 43.7% of male and 49.1% of female students reported using SNS for more than three hours per day. The mean score for social anxiety was 20.20, indicating a severe level of social anxiety among the study participants. Based on the responses of the sample study, the results showed an increase in negative indicators associated with SNSu and these unfavorable indicators were accompanied by an increase in the level of social anxiety.